Analisis Implementasi Akad Pembiayaan Mudharabah dan Musyarakah pada Bank Umum Syariah di Kota Bandung - Sulanjana, Rukanda Ahmad (Banking & Management Review, 2020)
Islamic Banks is a community trust institution in which its business is based on sharia principles. And what is in the spotlight nowadays on Islamic banks is not only based on their performance and performance results, but in terms of conformity with sharia principles is also a matter of great concern. Especially in Indonesia, Islamic banks in establishing partnerships and business cooperation with the community should partner more with the principle of profit sharing, namely by using the mudharabah and musyarakah financing agreements. The purpose of this study is to find out and analyze the suitability of the implementation of mudharabah and musyarakah financing agreements implemented by Islamic Commercial Banks in Bandung with the principles of sharia law and syariah banking operational systems for mudharabah and musyarakah financing applicable in Indonesia. Based on the results of the study using Qualitative Descriptive Analysis research methodology, the results show that the implementation of mudharabah and musyarakah financing schemes in Islamic commercial banks in the city of Bandung in terms of features and operational mechanisms are in accordance with the principles of Islamic law and Islamic banking operating systems that apply in Indonesia. . Keywords: Financing Agreement, Islamic Bank, Mudharaba and Musharaka Implementation